2020
DOI: 10.1038/s41467-019-14028-x
|View full text |Cite
|
Sign up to set email alerts
|

JMJD3 and UTX determine fidelity and lineage specification of human neural progenitor cells

Abstract: Neurogenesis, a highly orchestrated process, entails the transition from a pluripotent to neural state and involves neural progenitor cells (NPCs) and neuronal/glial subtypes. However, the precise epigenetic mechanisms underlying fate decision remain poorly understood. Here, we delete KDM6s (JMJD3 and/or UTX), the H3K27me3 demethylases, in human embryonic stem cells (hESCs) and show that their deletion does not impede NPC generation from hESCs. However, KDM6-deficient NPCs exhibit poor proliferation and a fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 66 publications
(74 reference statements)
2
35
0
Order By: Relevance
“…In the process of neurogenesis, we find that H3K27me3 levels were unchanged in the hESCs after the loss of UTX , and the differentiation potential of UTX KO hESCs to hNPCs is not affected. This finding supports the idea that maintaining the level of H3K27me3 may be important for the early stage of neurogenesis ( Shan et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…In the process of neurogenesis, we find that H3K27me3 levels were unchanged in the hESCs after the loss of UTX , and the differentiation potential of UTX KO hESCs to hNPCs is not affected. This finding supports the idea that maintaining the level of H3K27me3 may be important for the early stage of neurogenesis ( Shan et al., 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…The 53BP1-UTX interaction is required to upregulate key neurodevelopmental genes during the differentiation of human embryonic stem cells into neurons [37]. Yet another very recent investigation showed that knockout of UTX and/or JMJD3, encoding for another demethylase located on chromosome 17, determines the fidelity and lineage specification of human neural progenitor cells [38]. In their experiments they used hESC-H1, a male cell line, which means that the UTY gene is present.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that Oct1 recruits H3K27-specific demethylases to lineage-specific bivalent genes to mediate their induction during differentiation. One such demethylase is Utx/Kdm6a (Cloos et al 2008), which has been shown to regulate neuronal differentiation (Shan et al 2020). In ChIP-qPCR experiments at the same Pax3 promoter, Utx was enriched at D6 of MD differentiation (Fig.…”
Section: Resultsmentioning
confidence: 99%